The effect of food prices and household income on the British diet - Paola De Agostini (University of Essex, Institute for Social and Economic Research (ISER), 2014)
This paper investigates the effect of price variations on the diet composition in Britain. It describes the dynamics of food demand in relation to food prices over time using data from the British National Food Survey (NFS) covering the period 1975-2000. Demand elasticities with respect to price elasticities are estimated by solving a quadratic almost ideal demand system (QUAIDS) model controlling also for total expenditure on food, region of residence, household size, age of head of household, whether women are working, number of time in which the household buys ready food, household type and income quartiles. Focusing on the consumption technology function, effects of food price variation on calories intake, energy from fats and energy from carbohydrate have been explored deriving nutrients elasticities with respect to variation of food prices.
Keywords: D1; D12; H31; I18; 330; time-series of cross-section household survey data; food and nutrient demand and elasticities; prices; total food expenditures